Correction: Optimizing accuracy and efficacy in data-driven materials discovery for the solar production of hydrogen. Issue 4 (17th March 2022) - Xiong, Yihuang; Campbell, Quinn T.; Fanghanel, Julian; Badding, Catherine K.; Wang, Huaiyu; Kirchner-Hall, Nicole E.; Theibault, Monica J.; Timrov, Iurii; Mondschein, Jared S.; Seth, Kriti; Katz, Rebecca; Villarino, Andrés Molina; et al.
Abstract : Correction for 'Optimizing accuracy and efficacy in data-driven materials discovery for the solar production of hydrogen' by Yihuang Xiong et al., Energy Environ. Sci., 2021, 14, 2335–2348; DOI: ; 10.1039/D0EE02984J .